KONTRIBUSI PEMIKIRAN ABU NASR MANSUR IBN ‘ALI IBN ‘IRAQ AL-JA’DI(960 M – 1036 M) PADA MATERI TRIGONOMETRI - Andi Nurfadilah Armi; Nursalam Nursalam; Mardhiah Mardhiah; St Ibrah Mustafa Kamal (Muslim Heritage, 2022)
AbstractThis study aims to determine the contribution of the thoughts of Abu Nasr Mansur ibn 'Ali ibn 'Iraq Al-Ja'di (960 AD - 1036 AD) on trigonometric material. This research is a library research using library research data collection techniques or document review regarding Abu Nasr Mansur ibn 'Ali ibn 'Iraq Al-Ja'di. Abu Nasr Mansur is a Muslim scientist who has produced many monumental works in the fields of mathematics and astronomy. Abu Nasr Mansur is the founder of the law of sine on a plane and the law of sine of the sphere. The use of the law of sine on a flat plane in daily life based on the field is divided into two, namely in the field of civil engineering it is used to calculate building heights, calculate distances between two places and calculate aircraft heights; Meteorology is used to model cyclical trends, such as weather patterns and seasonal variations. The usefulness of the law of sine on a flat plane is used in the field of astronomy to determine the direction of prayer Qibla and prayer times.  AbstrakPenelitian ini bertujuan untuk mengetahui kontribusi pemikiran Abu Nasr Mansur ibn ‘Ali ibn ‘Iraq Al-Ja’di (960 M – 1036 M) pada materi trigonometri. Penelitian ini merupakan penelitian kepustakaan atau Library Research dengan menggunakan teknik pengumpulan data telaah kepustakaan atau telaah dokumen mengenai Abu Nasr Mansur ibn ‘Ali ibn ‘Iraq Al-Ja’di. Abu Nasr Mansur merupakan seorang ilmuan muslim yang telah menghasilkan banyak karya yang monumental dalam bidang matematika dan astronomi. Abu Nasr mansur merupakan penemu hukum sinus pada bidang datar dan hukum sinus bola. Kegunaan hukum sinus pada bidang datar dalam kehidupan sehari-hari berdasarkan bidangnya dibagi menjadi dua, yaitu pada bidang ilmu teknik sipil digunakan untuk menghitung tinggi gedung, menghitung jarak antar dua tempat dan menghitung ketinggian pesawat; pada bidang ilmu meteorologi digunakan untuk memodelkan tren siklus, seperti pola cuaca dan variasi musiman. Kegunaan hukum sinus pada bidang datar digunakan pada bidang astronomi untuk menentukan arah kiblat sholat dan waktu shola